Fire and Safety Standard of Indian Hospitals: A Lesson from AMRI - Kolkata Incidence - Editor in Chief (Al Ameen Medical College, 2012)
Recent devastating fire in AMRI, one of the five star hospitals in Kolkata, India has shaken entire medical professionals, administrators and Governments. The possible violation of fire safety norm in this hospital which took ninety two lives needs a serious thinking regarding hospital fire safety in India or elsewhere in the world